A cross sectional study to assess the prevalence of malocclusion in 08-12 years old school age children of the selected urban & rural community of Bangladesh (Update Dental College Journal, 2021)
Objective: To determine the prevalence of malocclusion in school-age children from a selective area of the urban and rural community of Bangladesh.Methods: A cross-sectional descriptive survey was conducted among 748 children aged 08-12 years old were examined from October 2019 to September 2020 in Sylhet Sardar Upazila, Bangladesh. Angle”s classification was used for recording molar relationship with malocclusion traits. The study participants were examined by disposable dental tools (calibrated probs and mirror) including torchlight. After the collection of all data, it was compiled and analyzed by Statistical Package for the Social Sciences (SPSS) Windows version 23. Chi-square test was used for categorical variables. P values